RESPON PEMBERIAN PUPUK KOTORAN KELINCI UNTUK MENINGKATKAN PERTUMBUHAN BIBIT MERANTI TEMBAGA (ShorealeprosulaMiq.) - Diana Wati; M. Mardhiansyah; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
ShorealeprosulaMiqis one of the tree’s main producers of wood in Indonesia and is a type of shorea that has faster growth until the age of 20 years compared to shorea. Shorealeprosulacan grow on peat soil. To increase the fertility of peat soil, it is necessary to add fertilizer, be it chemical fertilizers and organic fertilizers. Organic fertilizers can be obtained from manure rabbits. Rabbit droppings are not widely used by breeders, whileRabbit droppings and urine are good fertilizers that can improve physical properties, soil chemistry and biology. The purpose of this study was to determine the responseof rabbit manure fertilizer and find out the best composition of rabbit manure on peat medium on the growth of Shorealeprosulaseedlings. This research using a completely randomized design consisting of five treatments with five tests. The data obtained were then analyzed using fingerprints variance with SPSS software and further tested using the DNMRT test on 5% level. Giving rabbit manure has an effect on growth copper meranti seeds and the best composition to increase growth Shorealeprosulaseeds on peat medium is 60% rabbit manure fertilizer + 40% peat soil (Treatment D4) with a yield ofincrease height 0,91 cm, increase in diameter 0,12 mm, and top rootratio 3,25. Keywords: ShorealeprosulaMiq, rabbit manure, fertilizer, peat soil.